2014
DOI: 10.1016/j.joca.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression study of normal and damaged cartilage in anteromedial gonarthrosis, a phenotype of osteoarthritis

Abstract: SummaryObjectiveTo identify osteoarthritis (OA) relevant genes and pathways in damaged and undamaged cartilage isolated from the knees of patients with anteromedial gonarthrosis (AMG) – a specific form of knee OA.DesignCartilage was obtained from nine patients undergoing unicompartmental knee replacement (UKR) for AMG. AMG provides a spatial representation of OA progression; showing a reproducible and histologically validated pattern of cartilage destruction such that damaged and undamaged cartilage from withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 45 publications
1
63
1
Order By: Relevance
“…ADAM12 is the ADAM most consistently reported to display increased expression in human OA cartilage10, 11, 12, 15, 16, 17, 62. Its expression is reported to correlate with Mankin score 62 , and increased expression has also been reported in mice 2 weeks after DMM surgery 7 .…”
Section: Adamtssmentioning
confidence: 99%
“…ADAM12 is the ADAM most consistently reported to display increased expression in human OA cartilage10, 11, 12, 15, 16, 17, 62. Its expression is reported to correlate with Mankin score 62 , and increased expression has also been reported in mice 2 weeks after DMM surgery 7 .…”
Section: Adamtssmentioning
confidence: 99%
“…In the present study, we demonstrated the negative effect of PNE on IGF1 signaling and matrix genes expression. Due to the critical role of IGF1 signaling in promoting proteoglycan and collagen network formation, and thereby improving mechanical properties, a reduction of IGF1 signaling was associated with OA progression (35, 36). It is possible that reduced IGF1 signaling mediate the toxic effect of PNE on cartilage development.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, comparison between damaged and undamaged areas of the condyle, as described in (Snelling et al . ), shows expression patterns of genes involved in cell signalling, extracellular matrix remodelling and inflammatory responses; these include matrix metalloproteinases (MMPs), growth factor signalling proteins, collagens and SOX 9, amongst other common OA genes (Sato et al . ; Geyer et al .…”
Section: Separating Initiation and Progression Phases Using Human Tismentioning
confidence: 99%
“…The use of such protocols has identified various pathways and molecular markers for early and late OA. Indeed, comparison between damaged and undamaged areas of the condyle, as described in (Snelling et al 2014), shows expression patterns of genes involved in cell signalling, extracellular matrix remodelling and inflammatory responses; these include matrix metalloproteinases (MMPs), growth factor signalling proteins, collagens and SOX 9, amongst other common OA genes (Sato et al 2006;Geyer et al 2009). Fukui et al (2008) have separated the severity of degradation by grouping the samples (from the same OA patients' joint) into four distinct areas depending on the zones of the articular cartilage affected (preserved area, damaged with superficial, middle and deep zones present, damaged with middle and deep zones, damaged with deep zones only).…”
Section: Separating Initiation and Progression Phases Using Human Tismentioning
confidence: 99%